Web-based application for real-time environment monitoring systems using wireless sensor network - Ian Kamajaya (2009)
Wireless Sensor Network (WSN) technology is one of the most emerging technologies in this century. Unlike its predecessor wireless network technologies, infrastructure-based wireless networks and ad-hoc wireless networks, wireless sensor network technology provide maximum application’s flexibility with minimum price and power consumption. One of the common methods used in system monitoring nowadays is through website. This is due to the rapid advancement in technology that allows personal computer (PC) to perform extremely fast computation and the invention of Internet and World Wide Web that enable users to share information through multiple channels. As web application becomes more common, so does its usage as system monitoring tool.